Effectiveness of lidocaine patches in the treatment of post-herpetic neuralgia on the face: a systematic review and meta-analysis (Research, Society and Development, 2021)
The post-herpetic neuralgia (PHN) is one of the most chalenging neuropathies to resolve. There are many treatment options with varying degrees of effectiveness. This paper conducts a systematic review of the literature on lidocaine patches in the treatment of these neuralgia.  A systematic review according to the PRISMA guidelines on lidocaine patches in the treatment of postherpetic neuralgia. The PROPERO registration has been carried out. A meta-analysis was performed with RevMan 5.3. Nine articles were included according to criteria. A table of excluded articles and their reason was carried out. Lidocaine patches are effective in treating post-herpetic neuralgia and are safer than other treatments, making them available for elderly patients with co-morbid conditions when other treatments cannot be used due to side effects. Lidocaine patches should be considered the first line therapy in the treatment of post-herpetic neuralgia of the face because of their safety and cost-benefit ratio.